Social cost of premature deaths due to COVID-19 in Peru - Curro-Urbano, Olga María (2022)
Background: The human cost of the COVID-19 pandemic is significant, but the true impact is still uncertain. Objetive: To determine the years of potential life lost and the social cost of death due to the COVID-19 disease in the Peruvian population. Material and Methods: An observational and descriptive study was carried out, through the secondary analysis of deaths due to COVID-19 in Peru between January 1, 2020, and July 31, 2021, reported by the Ministry of Health of Peru. Results: During 2020, 926,343.5 years of life were lost in Peru; however, between January 1 and July 31, 2021, 1,116,553.1 years had already been lost. From the start of the pandemic until July 31, 2021, the social cost of deaths due to COVID-19 has amounted to USD 18,807,942,464.6. Conclusion. The COVID-19 pandemic has caused a high loss of potential years of life and high social cost, mainly in urban territories with higher economic development.